(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The study focuses on the unique confluence of aesthetic appeal and performing skills of Kathakali; as elite and prestigious form of theatre from Kerala. Through an inept analysis of its historic, thematic, and cultural contents, the paper examines how satire, love, and other basis human emotions are evoked. Renowned for its elaborate costumes, dynamic dense, captivating music and powerful story telling. Kathakali serves as a living repository of reframed as well as cultural heritage. The paper also delves in to the performative elements such as music, dance, gestures, choreography, use of instruments, that contribute to its aesthetic appeal. Through this examinate the paper underscores Kathakali’s role in maintaining the aesthetic appeal and its capacity of fostering a deeper understanding of historical and mythological consciousness of current cultural scenario.